The Concept of Stringency for Test Comparison: The Case of a Cauchy Location Parameter - Arif Zaman; Asad Zaman; Atiq-ur- Rehman (International Econometric Review (IER), 2017)
Strategies for comparison of alternative tests do not receive much attention in econometrics. The purpose of this paper is to introduce the concept of stringency and illustrate it in the context of a very simple hypothesis testing problem. Systematic use of this concept can be very helpful in evaluating relative performance of tests
Keywords: C12; 330; Power Envelope; Location Parameter; Stringent Test